Training of Pakwalisanak Cadres (Guardians of Clean Water and Adequate Sanitation) to Accelerate Stunting Reduction in Demak Regency - Prasetyo, Eko; Caesar, David Laksamana; Cahyanti, Luluk (PT FORMOSA CENDEKIA GLOBAL, 2023)
Nutritional problems in toddlers are a public health problem that is still relatively high in Indonesia. Several factors cause the incidence of stunting, apart from the mother's lack of knowledge about nutrition before and during pregnancy, as well as inappropriate child rearing patterns, namely lack of access to clean water and proper sanitation. Objective: Carrying out training for Pakwalisanak cadres (Fathers of Clean Water and Adequate Sanitation) to accelerate the reduction of stunting in Demak Regency Method: The method of community service in this activity is in the form of training. The method of implementing this service program includes counseling and discussions about the importance of clean water and proper sanitation, as well as the formation of Pakwalisanak cadres (Fathers of Clean Water Guards and Decent Sanitation) to accelerate the reduction of Stunting in Demak Regency. Results: Community service activities, training and formation of pakwalisanak cadres, were attended by 20 participants from 10 Stunting locus villages in Demak Regency. All participants were very enthusiastic about taking part in the training, discussions and formation of Pakwalisanak Cadres and were committed to reducing stunting in Demak Regency. Conclusion: Community service activities in the form of training and formation of Pakwalisanak cadres are very useful for accelerating the reduction of stunting in Demak Regency.